Analisis Respon Peserta didik Terhadap Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Reciprocal Teaching - Magfiroh, Siti; Marhaeni, Nafida Hetty (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The research objective is to determine students' responses to the use of Student Worksheets (LKPD) in mathematics learning. The instruments used in this study are student response questionnaires and Reciprocal Teaching-based LKPD. The population for this research is students of SMA Negeri 4 Yogyakarta in class XI MIPA 2. The sample consists of 32 students. The results of this study indicate that Reciprocal Teaching-based LKPD received very good overall responses. From the scale test, think-pair-share-based LKPD received good responses, and from the high-level group (B2), Reciprocal Teaching-based LKPD received very good responses. Based on the analysis, it is known that each aspect of the student response questionnaire has an average value of > 71. This means that LKPD is practically used by students. Therefore, it can be concluded that LKPD is practically used by students in terms of suitability with the Reciprocal Teaching learning approach, with 4 items on question relevance, 4 items on interest, 6 items on material and presentation, and 3 items on language usage. This research will be continued to effectiveness phase